Ovarian cancer plasticity and epigenomics in the acquisition of a stem-like phenotype - Berry Nicholas B; Bapat Sharmila A (Journal of Ovarian Research, 2008)
Abstract Aggressive epithelial ovarian cancer (EOC) is genetically and epigenetically distinct from normal ovarian surface epithelial cells (OSE) and early neoplasia. Co-expression of epithelial and mesenchymal markers in EOC suggests an involvement of epithelial-mesenchymal transition (EMT) in cancer initiation and progression. This phenomenon is often associated with acquisition of a stem cell-like phenotype and chemoresistance that correlate with the specific gene expression patterns accompanying transformation, revealing a plasticity of the ovarian cancer cell genome during disease progression. Differential gene expressions between normal and transformed cells reflect the varying mechanisms of regulation including genetic changes like rearrangements within the genome, as well as epigenetic changes such as global genomic hypomethylation with localized promoter CpG island hypermethylation. The similarity of gene expression between ovarian cancer cells and the stem-like ovarian cancer initiating cells (OCIC) are surprisingly also correlated with epigenetic mechanisms of gene regulation in normal stem cells. Both normal and cancer stem cells maintain genetic flexibility by co-placement of activating and/or repressive epigenetic modifications on histone H3. The co-occupancy of such opposing histone marks is believed to maintain gene flexibility and such bivalent histones have been described as being poised for transcriptional activation or epigenetic silencing. The involvement of both-microRNA (miRNA) mediated epigenetic regulation, as well as epigenetic-induced changes in miRNA expression further highlight an additional complexity in cancer stem cell epigenomics. Recent advances in array-based whole-genome/epigenome analyses will continue to further unravel the genomes and epigenomes of cancer and cancer stem cells. In order to illuminate phenotypic signatures that delineate ovarian cancer from their associated cancer stem cells, a priority must lie in the expansion of current technologies and further implementation of bioinformatics to handle the complexity of the cancer epigenome and the various networks that coordinate disease initiation and progression. Great potential lies in the translation of these findings into epigenetic-based therapies. Additionally, targeting chemo-resistant cancer stem cells may provide a much needed breakthrough in treatment of advanced ovarian cancer and chemoresistant disease.